Coffee under threat - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Tracheomycosis or vascular wilt disease (Fusarium xylarioides) of toffee bas re-emerged as one of the most significant threats to the coffee industry in Central Africa. The fungus initially causes a characteristic spiral yellowing of the leaves...